Factors Affecting Performance of Indian Murrah Buffalo: A Review - Kumar, Vijay (Journal of Buffalo Science, 2015)
Murrah is one of the best buffalo breed in India. The success of Indian dairy industry is much dependent on productivity and efficient reproduction performance of Murrah buffaloes. The environmental factors are generally influenced the Murrahs’ performance as well as other breeds. The performance traits reviewed were first lactation 305-days or less milk yield, first lactation length, first lactation average daily milk yield, dry period, growth, age at first calving, first service period, calving interval, age at maturity, age at calving, days to first service, number of services per conception, breeding interval, breeding efficiency, conception rate and daughter pregnancy rate of Murrah buffalo. All the productive and reproductive traits were affected by herd, year and season of calving.